Conciliación de saldos de cartera en área financiera en Cnel Babahoyo año 2020-2021. - Cevallos Cabrera, Denisse Lisbeth (2022)
Service companies have become the most frequented today, thanks to the fact that they have collaborated for the development of the countries that are beginning to emerge in the world economy, through their companies, among which, the most notable is that of electricity. CNEL has been working in Ecuador for many years, and the fulfillment of its duty is focused on providing an excellent service without any inconvenience, but due to various reasons, the CNEL headquarters located in Babahoyo is having registration problems on its financial activity, a problem that has been known for some years. This research shows the different aspects that are important to keep a correct record of financial movements, as well as the techniques indicated to do it through the skills obtained in the career as well as the necessary tools to discover the reasons and factors that without those responsible for have CNEL Babahoyo in the current situation.